Evaluation of Humoral Immunity to SARS-CoV-2: Diagnostic Value of a New Multiplex Addressable Laser Bead Immunoassay - Drouot, Laurent; Hantz, Sébastien; Jouen, Fabienne; Velay, Aurélie; Lamia, Bouchra; Veber, Benoit; Sibilia, Jean; Lotellier, Marlène; Candon, Sophie; Alain, Sophie; Fafi-Kremer, Samira; Boyer, Olivier (Frontiers in Microbiology, 2020)
Despite efforts to develop anti–severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody (Ab) immunoassays, reliable serological methods are still needed. We developed a multiplex addressable laser bead immunoassay (ALBIA) to detect and quantify anti-Spike S1 and nucleocapsid N Abs. Recombinant S1 and N proteins were bound to fluorescent beads (ALBIA-IgG-S1/N). Abs were revealed using class-specific anti-human Ig Abs. The performances of the test were analyzed on 575 serum samples including 192 from SARS-CoV-2 polymerase chain reaction–confirmed patients, 13 from seasonal coronaviruses, 70 from different inflammatory/autoimmune diseases, and 300 from healthy donors. Anti-S1 IgM were detected by monoplex ALBIA-IgM-S1. Comparison with chemiluminescent assays or enzyme-linked immunosorbent assays was performed using commercial tests. Multiplex ALBIA-IgG-S1/N was effective in detecting and quantifying anti–SARS-CoV-2 IgG Abs. Two weeks after first symptoms, sensitivity and specificity were 97.7 and 98.0% (anti-S1), and 100 and 98.7% (anti-N), respectively. Agreement with commercial tests was good to excellent, with a higher sensitivity of ALBIA. ALBIA-IgG-S1/N was positive in 53% of patients up to day 7, and in 75% between days 7 and 13. For ALBIA-IgM-S1, sensitivity and specificity were 74.4 and 98.7%, respectively. Patients in intensive care units had higher IgG Ab levels (Mann–Whitney test, p < 0.05). ALBIA provides a robust method for exploring humoral immunity to SARS-CoV-2. Serology should be performed after 2 weeks following first symptoms, when all COVID-19 (coronavirus disease 2019) patients had at least one anti-S1 or anti-N IgG Ab, illustrating the interest of a multiplex test.